2004
DOI: 10.1021/cm035222l
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Electrical Properties of Highly (111)-Oriented (Na0.5Bi0.5)TiO3 Thin Films by a Sol−Gel Process

Abstract: Sodium bismuth titanate, (Na0.5Bi0.5)TiO3 (NBT), thin films were grown on Pt/Ti/SiO2/Si substrates via a sol−gel process. The precursor solution for spin-coating was prepared from bismuth nitrate, sodium acetate, and titanium n-butoxide as starting materials, and acetic acid and methanol as solvents, and pervoskite NBT films with high (111)-orientation have been obtained. The Au/NBT/Pt thin film capacitor showed a hysteresis loop at an applied electric field of 200 kV/cm with remanent polarization (P r) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 30 publications
3
42
0
Order By: Relevance
“…The films contained mixed phases including the pyrochlore Bi 2 Ti 2 O 7 (BTO) and the perovskite NBT. Many studies of the preparation of bulk ceramics 10) and thin films 6) have reported that the preferred pyrochlore BTO phases are often created. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The films contained mixed phases including the pyrochlore Bi 2 Ti 2 O 7 (BTO) and the perovskite NBT. Many studies of the preparation of bulk ceramics 10) and thin films 6) have reported that the preferred pyrochlore BTO phases are often created. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3,4) However, it has been reported that a stable single perovskite NBT phase is not easy to prepare due to the relatively low tolerance factor t ~ 0.799 and volatility of Na and Bi. 5,6) These problems result in the creation of secondary phases and the degradation of electrical performance. So until recently, various processes such as the compositional compensation and/or the ambient control have been widely reported with the aim of preparing pure perovskite NBT films.…”
Section: 2)mentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7] In spite of the numerous studies on BNT-based single crystals and ceramics, literature tackling with the growth and characterization of BNT-based, especially BNBT-based thin films, still remains at an infancy stage. [8][9][10][11][12] Consequently, doping effects on the electrical properties of thin film BNBT materials are still unclear. Abazari et al 13 has recently reported epitaxial potassium modified BNBT thin films grown on SrRuO 3 coated SrTiO 3 substrates by pulsed laser deposition ͑PLD͒.…”
mentioning
confidence: 99%